Milly, molly and betelguese - Pittar, Gill (Milly Molly Books Place of publication not identified, 2003)
Milly and Molly watch a mother guinea pig as she tells each of her offspring the meaning of their name. Betelgeuse however has no story until Milly and Molly see the star. Suggested level: junior